Stephenson enterprises: a business plan - Stephenson, Edward (Kansas State University, 2010)
A business plan serves two main functions: One is to provide a set of guidelines and expectations for running the business and the other would be to request funding from either a traditional or non-traditional lending source. Most business plans consist of the executive summary, business description, market analyses, management team, operations, and financial projections. Stephenson Enterprises is in the process of obtaining funding for a start-up business that will manufacture a biodegradable low cost substitute loose-fill packaging material. Due to the relatively high cost of this start-up, external funding is necessary. The first choice is to approach a large bank with the business plan, secondary choices if necessary would include smaller banks. The third choice would be alternative funding such as nonprofit organizations that provide start-up funding, however many of these are limited in the amount they lend. In order to garner funding for this entrepreneurship, it was decided that a business plan was needed. A business plan has two primary functions. One function is to set forth some guidelines as to how a firm is operated as well as what is projected. The second, and perhaps most often the reason a business plan is developed is to secure funding from a financial institution. Within the business plan a myriad of financial data was gathered to include: financial analysis, financial projections, cash flow, balance sheet, break-even analysis, sales proforma, income statements and sensitivity analyses. In addition to the financial data, a market analysis was conducted to provide insight into the local market. This business plan will not only provide an estimate of financials but will also serve as a guide book for operating the business.
Keywords: Packing material; Business plan; Blodegradable; Business concept; Package shipping; Marketing plan; Economics, Agricultural (0503)